Metal‐Organic Chemical Vapor Deposition (MOCVD) Synthesis of Heteroepitaxial Pr0.7Ca0.3MnO3 Films: Effects of Processing Conditions on Structural/Morphological and Functional Properties. Issue 4 (5th June 2015) - Catalano, Maria R.; Cucinotta, Giuseppe; Schilirò, Emanuela; Mannini, Matteo; Caneschi, Andrea; Lo Nigro, Raffaella; Smecca, Emanuele; Condorelli, Guglielmo G.; Malandrino, Graziella
Abstract Calcium‐doped praseodymium manganite films (Pr0.7Ca0.3MnO3, PCMO) were prepared by metal‐organic chemical vapor deposition (MOCVD) on SrTiO3 (001) and SrTiO3 (110) single‐crystal substrates. Structural characterization through X‐ray diffraction (XRD) measurements and transmission electron microscopy (TEM) analyses confirmed the formation of epitaxial PCMO phase films. Energy dispersive X‐ray (EDX) and X‐ray photoelectron spectroscopy (XPS) characterization was used to confirm lateral and vertical composition and the purity of the deposited films. Magnetic measurements, obtained in zero‐field‐cooling (ZFC) and field‐cooling (FC) modes, provided evidence of the presence of a ferromagnetic (FM) transition temperature, which was correlated to the transport properties of the film. The functional properties of the deposited films, combined with the structural and chemical characterization collected data, indicate that the MOCVD approach represents a suitable route for the growth of pure, good quality PCMO for the fabrication of novel spintronic devices.